Evaluating Communication Patterns of Women Legislative Successors of Karawang in 2019 Election - Mayasari Mayasari; Nani Darmayanti; Yanti Tayo; Zainal Abidin; Kusrin Kusrin (Nyimak: Journal of Communication, 2022)
IIn the dynamics of general elections, the discussion of women legislative candidates has always been an interesting topic because the proportion of 30% of women candidates’ minimum requirement is always difficult to fulfill by any political party. The difficulty of women legislative candidates penetrating parliamentary seats is a problem that must be resolved. Therefore, it is necessary to conduct qualitative research to formulate how the communication patterns carried out by women politicians in the Karawang Regency, who have succeeded in penetrating parliamentary seats through case study techniques during the research. The communication pattern that marks the women’s success in election contestation can be a guide or reference when other women party politicians enter politics and advance to become legislature members. This research is limited to women members of the legislature who come from the Golkar Party. The results showed that the success of women members of the Regional Legislative Assembly (DPRD) from the Golkar party in occupying seats in the DPRD was partly due to the communication patterns they succeeded in establishing. They build vertical, horizontal, formal, and informal communication patterns that apply more social and cultural approaches. The uniqueness is when social media is used as a tool for political campaigns today, the communication strategy developed by those women legislative candidates of the Golkar party does not take advantage of social media. This is because the targeted constituents are people in remote areas, so the communication pattern through a direct face-to-face approach is much more impactful than social media.Keywords: Women DPRD members of Karawang Regency, political communication patterns, 2019 general election ABSTRAKDalam dinamika pemilihan umum (pemilu) pembahasan mengenai calon anggota legislatif perempuan selalu menjadi topik yang menarik karena adanya proporsi 30% caleg perempuan yang selalu sulit dipenuhi oleh setiap partai politik. Sulitnya calon anggota legislatif perempuan menembus kursi parlemen merupakan masalah yang harus dicarikan solusinya. Dengan demikian, perlu dilakukan penelitian dengan menggunakan metode kualitatif untuk merumuskan bagaimana pola komunikasi yang telah dilakukan oleh para politisi perempuan di Kabupaten Karawang yang telah berhasil menembus kursi parlemen dengan studi kasus sebagai teknik penelitian. Pola komunikasi yang menandai keberhasilan kaum perempuan dalam kontestasi pemilu ini dapat menjadi pedoman ataupun acuan ketika pihak lain yang juga perempuan akan terjun ke dunia politik dan akan maju menjadi anggota legislatif. Penelitian ini dibatasi hanya pada anggota legislatif perempuan yang berasal dari Partai Golkar. Hasil penelitian  menunjukkan bahwa keberhasilan para anggota DPRD perempuan dari Partai Golkar dalam menduduki kursi di DPRD salah satunya disebabkan oleh pola komunikasi yang berhasil mereka bangun. Adapun pola komunikasi yang mereka bangun tersebut adalah pola komunikasi vertikal, horizontal, formal, informal yang lebih cenderung menerapkan pendekatan sosial dan budaya. Saat media sosial dijadikan alat kampanye politik dewasa ini, strategi komunikasi yang dibangun para calon anggota legislatif perempuan di Kabupaten Karawang yang berasal dari Partai Golkar ini tidak memanfaatkan media sosial. Hal ini disebabkan konstituen yang menjadi sasarannya adalah masyarakat pelosok yang belum memiliki pemahaman awam terhadap teknologi sehingga pola komunikasi melalui tatap mula langsung jauh lebih berdampak dibandingkan dengan penggunaan media sosial.Kata Kunci: Anggota DPRD perempuan Kabupaten Karawang, pola komunikasi politik, Pemilu 2019